Akses Pemakaman untuk Kelompok Agama Minoritas - Bimantara, Arya; Phahlevy, Rifqi Ridlo (ResearchJet Journal of Analysis and Inventions, 2024)
That this study focused on find out of what kind of access to funeral facilities that provided by the Indonesian’s Government to the pople who are in minority religious groups in general and to examine wether the granting of that access is appropriate and meets the standart aspects of justice and national constitutional rights or not. This research was conducted using a socio-legal method and using a statue approach. As the result of this study, indicates that the granting of access to funeral facilities by the Government for religious minority group still does not fully fulfill the standart aspects of justice and also the national constitutional rights in a minor part, but already fulfill the major aspects.